Two new diarylheptanoids and a new phenylhexanol derivative from the bulbils of Dioscorea opposita Thunb. and their α-glucosidase inhibitory activity. (August 2021) - Cao, Yangang; Li, Hongwei; Hao, Zhiyou; Guo, Menghuan; Ren, Yingjie; Liu, Yanling; Wang, Mengna; He, Chen; Chen, Xu; Fan, Xiling; Zheng, Xiaoke; Feng, Weisheng
Graphical abstract: Highlights: Two new diarylheptanoids (1 –2 ) and a new phenylhexanol derivative (3 ), along with seven known compounds (4 –10 ) were isolated from the bulbils of Dioscorea opposita Thunb.. The absolute configurations of compounds 1 –2 were deduced by comparison of the experimental and calculated ECD spectra. The α -glucosidase inhibitory effects of all the isolated compounds were evaluated. Molecular docking and molecular dynamics simulations of compound 7 bound α -glucosidase were performed Abstract: Two previously undescribed diarylheptanoids, diosniponol E (1 ) and F (2 ), and a new phenylhexanol derivative, (rel-2 R, 4 R )-6-(4-hydroxy-3-methoxyphenyl)-hexane-1, 2, 4-triol (3), together with seven known compounds, were isolated from the bulbils of Dioscorea opposita Thunb.. Their structures were elucidated by HRESIMS and 1D/2D NMR as well as by comparison with the literature, and absolute conﬁgurations of compounds 1 and 2 were deduced by comparison of their experimental and calculated electronic circular dichroic (ECD) spectra. All the isolated compounds were evaluated in vitro for their α -glucosidase inhibitory activity. The results indicated that compounds 3 and 7 exhibited inhibitory effect against α -glucosidase with the IC50 values of 16.2 ± 2.2 and 8.7 ± 1.6 μ M, respectively. Molecular docking experiments were performed to identify the probable binding mode of compound 7 in the binding sites of α -glucosidase and molecular dynamics simulations were performed to evaluate the stability over time of the main interactions observed in docking experiments.